2019
DOI: 10.1021/jacs.9b02075
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Replication, Transcription, and Translation in a Semi-Synthetic Organism

Abstract: Previously, we reported the creation of a semi-synthetic organism (SSO) that stores and retrieves increased information by virtue of stably maintaining an unnatural base pair (UBP) in its DNA, transcribing the corresponding unnatural nucleotides into the codons and anticodons of mRNAs and tRNAs, and then using them to produce proteins containing non-canonical amino acids (ncAAs). Here we report a systematic extension of the effort to optimize the SSO by exploring a variety of deoxy-and ribonucleotide analogs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…To p: The isoC-isoG base pair which was the first developedu nnatural base pair. [5] Z and P as well as S and B are two unnatural base pairs which were developed by Benner et al [6,7] Middle:H ydrophobic base pairs (NaM and TPT3)w hich was developed by Romesberg et al [2] and the TPT3 CP and NaM base pair which was developed by Kath-Schorr et al [8] Bottom:The kappa (k k)xanthosine (X)b ase pair used in this paper. Buchwald-Hartwig coupling to obtain the benzoyl-protected pyrimidine diamine, which was first appliedb yW agenknecht et al [14] shows increased selectivity when the C5 of the ribose is silylated.…”
Section: Synthesis Of Kappa Base Phosphoramiditementioning
confidence: 99%
See 2 more Smart Citations
“…To p: The isoC-isoG base pair which was the first developedu nnatural base pair. [5] Z and P as well as S and B are two unnatural base pairs which were developed by Benner et al [6,7] Middle:H ydrophobic base pairs (NaM and TPT3)w hich was developed by Romesberg et al [2] and the TPT3 CP and NaM base pair which was developed by Kath-Schorr et al [8] Bottom:The kappa (k k)xanthosine (X)b ase pair used in this paper. Buchwald-Hartwig coupling to obtain the benzoyl-protected pyrimidine diamine, which was first appliedb yW agenknecht et al [14] shows increased selectivity when the C5 of the ribose is silylated.…”
Section: Synthesis Of Kappa Base Phosphoramiditementioning
confidence: 99%
“…Many of these techniquesu se the standard approach of in vitro transcriptiont og enerate RNA, and employ an additional base pair that is orthogonal to the two Watson-Crick-like base-pairs that establish sequence specificity during transcription. [1][2][3][4] Twom ain strategies have been previously reported:e ither larger hydrophobic moieties establish an entirely novel complementary system or the hydrogen bonding pattern of the standardp urine and pyrimidine-based scaffolds are expanded. Both these strategies have generated additional, orthogonal base-pairs that can be employed to different degrees in in vitro applications or for genetic code expansion in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction cleanly furnished the DNA-BSA conjugate (53) and ESI-TOF analysis of the crude reaction mixture indicated that no unmodified BSA remained in solution. 51,52 Conjugation to serum albumin is a valuable half-life increasing strategy that is commonly employed in the context of readily-cleared peptide and small protein drugs, and could in principle be applied to next-generation ASOs. [53][54][55][56][57] SENDR was also used to create a DNA construct that could be used in site-specific antibody conjugations ( Figure 6B).…”
Section: Sendr: Dna-protein Conjugatesmentioning
confidence: 99%
“…The well-known double helical structure adopted by DNA arises through specific Watson-Crick interactions and packing forces between the four canonical nucleobases A, C, G, and T. However, a combination of organic chemistry and polymerase engineering have not only permitted to broaden the horizon of applications of DNA to fields that markedly deviate from its natural role [1][2][3][4][5][6][7][8][9][10][11][12] but also to expand the genetic alphabet by one [13][14][15][16] or multiple [17] orthogonal, artificial base pairs. Unnatural base pairs (UBPs) that have been used in this context mainly consist of large aromatic residues that interact via hydrophobic and packing forces, [18] nucleobases with alternative hydrogen bond patterns, [17] and nucleoside analogs capable of interacting through shape complementarity. [19,20] More recently, artificial metal base pairs have been proposed as alternative scaffolds for the construction of UBPs.…”
Section: Introductionmentioning
confidence: 99%